SOME AGROBIOLOGICAL PECULIARITIES AND POTENTIAL USES OF GLYCYRRHIZA GLABRA L. AND ONOBRYCHIS ARENARIA (KIT.) DC. IN THE REPUBLIC OF MOLDOVA - Victor ŢÎŢEI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The agrobiological features, the quality of the green mass and haylage from the local ecotype of Glycyrrhiza glabra and Onobrychis arenaria have been the subject of a recent study. It has been found that the dry matter of harvested green mass of the studied crops contained 162-167 g/kg CP, 302-307 g/kg CF, 88-100g/kg CA, 467-471 g/kg NDF, 317-321 g/kg ADF, 48-54 g/kg ADL, 267-269 g/kg Cel, 150 g/kg HC, 100-103 g/kg TSS, 64.7-67.7 % DDM, 54.3- 59.9 % ODM, RFV= 125-127, 10.23-10.28 MJ/kg ME and 6.34-6.56 MJ/kg NEl. The biochemical composition of the dry matter of the haylage and its nutritive value: 155-184 g/kg CP, 267-301 g/kg CF, 114-123 g/kg CA, 429-550 g/kg NDF, 299.333 g/kg ADF, 47-50 g/kg ADL, 249-288 g/kg Cel, 130-187 g/kg HC, 79-91 g/kg TSS, 62.4-67.8 % DDM, 53.6-54.0 % ODM, RFV= 113-142, 10.20-10.57 MJ/kg ME and 6.20-6.59 MJ/kg Nel. We found that the studied substrates for anaerobic digestion have C/N=16.54-19.85, optimal amount of lignin and hemicelluloses, the biochemical methane potential varied from 283 to 301 l/kg ODM. The studied ecotype had optimal quality as fodder for livestock and as substrate for biomethane production.